Comparative Studies of Green Bonds Investment in the United States and Europe: Responding to Social Concern on Climate Change - S.P.H. Spencer Vitharana (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The oil and gas industry’s responsibilities regarding climate change are still debated on both sides of the Atlantic. Despite this debate, two-thirds of carbon dioxide emissions into the atmosphere are released from oil and gas related industries. In order to keep rising temperature down to Paris climate targets, global oil companies face numerous difficulties because they require larger investments to develop new technologies for a broader energy mix. Studies show that climate change is the biggest risk in terms of impacts on the global economy. Realizing the truth, some countries have already managed to break the link between economic growth and carbon dioxide emissions, but more decisive policies are needed to break the link by capable economies such as the United States and Europe. In that context, this paper explores the recent green investment trends in the US and Europe to see how public opinion influences green investment to reduce climate change risks. This study focuses on green bond investment, describing its progress and variation from 2016 to 2019in the United States and Europe. I use Excel spreadsheets to give graphical and numerical output in descriptive analysis. In conclusion, I found that public opinion on climate change significantly influenced green bond investment in both the US and Europe.